PERSPECTIVE ASPECTS OF OPTIMIZING RECREATIONAL NATURE MANAGEMENT WITHIN PRYUDAYSKYY AQUATIC-TERRAIN RECREATIONAL COMPLEX - KULINICH, Maryna; TRON, Nataliya (Ekonomichna ta Sotsialna Geografiya, 2016)
The article presents the basic aspects of the impact of recreational activities on the environment. Also, there was investigated the state of existing elements of organized recreation within Pryudayskyy aquatic-terrain recreational complex (ATRC) and was found objectively existing problems of recreation within it. This work in its basis based on several concepts, including the concept of functional zoning of recreational territories and the concept of recreational modules. Combining the fundamental positions of this two concepts, and, also, taking into account the state building codes of Ukraine about arranging of outdoor recreation - all of this allowed to propose concrete steps to optimize the functional organization of recreation within Pryudayskyy aquatic-terrain recreational complex. These steps are presented as a description of the proposed scheme of functional organization of recreation within the Pryudayskyy ATRC. In the developed scheme, there was presented individual recreational modules with different specialization and point elements of recreational improvement of the coastal area and aquatic area of Uday River at the site between villages Velyka Krucha and Deymanivka.

В статті представлено основні аспекти впливу рекреаційної діяльності на природне середовище, досліджено стан наявних елементів організованої рекреації в межах Приудайського аквально-террального рекреаційного комплексу та виявлено об’єктивно існуючі проблеми організації рекреації в його межах. Дана робота в своїй основі опирається на декілька концепцій, серед яких концепція функціонального зонування рекреаційних територій та концепція рекреаційних модулів. Поєднання фундаментальних позицій цих двох концепцій, а також врахування державних будівельних норм України по облаштуванню місць відпочинку на природі, дозволили запропонувати конкретні прикладні кроки по оптимізації функціональної організації рекреації в межах Приудайського аквально-террального рекреаційного комплексу. Ці кроки представлені у вигляді опису до запропонованої схеми функціональної організації рекреації Приудайського АТРК. На розробленій схемі представлено як окремі рекреаційні модулі з різною спеціалізацією, так і точкові елементи рекреаційного облаштування прибережної території і акваторії річки Удай на ділянці від с. Велика Круча до с. Дейманівка.
ПЕРСПЕКТИВНІ АСПЕКТИ ОПТИМІЗАЦІЇ РЕКРЕАЦІЙНОГО ПРИРОДОКОРИСТУВАННЯ В МЕЖАХ ПРИУДАЙСЬКОГО АКВАЛЬНО-ТЕРАЛЬНОГО РЕКРЕАЦІЙНОГО КОМПЛЕКСУ
Keywords: Pryudayskyy ATRC; recreational nature management; recreational module; functional zoning; state building codes of Ukraine; Приудайський АТРК; рекреаційне природокористування; рекреаційний модуль; функціональне зонування; державні будівельні норми України